If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 34x + 7 = 0 Reorder the terms: 7 + -5x + 34x = 0 Combine like terms: -5x + 34x = 29x 7 + 29x = 0 Solving 7 + 29x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 29x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 29x = 0 + -7 29x = 0 + -7 Combine like terms: 0 + -7 = -7 29x = -7 Divide each side by '29'. x = -0.2413793103 Simplifying x = -0.2413793103
| 67n=-22 | | 2p^3+p^2q+pq= | | -5p+2+6p=9 | | -694=.83r | | 2x^2+27x-5.1=0 | | -.125x=-4 | | .1b=-108 | | 3(4z-1)-5(z+1)=3(z+1) | | 3y-12=7 | | .05=.6m | | 3x^2+4+1= | | -.75k=.67 | | -13x^3+20x-7=0 | | 18=-.5t | | -4d+2(4+9)=-14 | | 0.083n=12 | | 9m-13=-22+8m | | 36y=108 | | x^3-x^2-1120=0 | | x=-3y^2-12y | | 3(x-4)-2(x+2)-13=-20 | | (3x-12)-2x+-2-13=-20 | | 3x-12-2x+4-13=20 | | 24x^3-21x^2= | | (3x-12)-2x+(-2)-13=-20 | | -4=8-s | | 2-(y+2)=y | | 46x^3+43x^2+5x= | | 2-(y+2)=ey | | 2x(x+3)=12 | | 3x-12+16=2x+10 | | X+5x=3 |